Photic zone redox oscillations and microbialite development recorded by Early Triassic sediments of the Perth Basin: A geochemical approach - Taniwaki, Takashi; Elders, Chris; Böttcher, M.E.; Holman, Alex; Grice, Kliti (PERGAMON-ELSEVIER SCIENCE LTD, 2022)
Photic zone euxinia (PZE) has previously been identified in the Early Triassic Kockatea Shale of the northern Perth Basin, based on the presence of biomarkers such as isorenieratane, which is derived from isorenieratene produced by green sulfur bacteria. However, green and purple sulfur bacteria can also occur in microbial mats. In this study we present a basin-scale assessment of biomarkers associated with open water column PZE and/or microbialites. The lithofacies from the Early Triassic of the northern part of the northern Perth Basin consist of dark coloured mudstones (black to dark grey) with microbialites, which were deposited away from basin margins. These samples are found to contain okenane, chlorobactane and isorenieratane derived from carotenoid pigments of purple, green-green and green–brown sulfur bacteria, respectively. These biomarkers are not observed in the light coloured mudstones (medium grey) formed under oxic conditions in a tidal environment with higher clastic input close to the basin margins in the southern part of the basin where shallow marine sandstones were also deposited. Okenane and chlorobactane were abundant in facies containing microbialites which developed in a shallow water setting on intra-basinal structural highs. The development of oxic conditions near the basin margins in the Perth Basin provided refuges for organisms during the end Permian mass extinction event. Okenane was more abundant in the microbialite facies compared with the dark coloured mudstones deposited under PZE. C33 n-alkylcyclohexane (n-C33 ACH) has previously been described as a biomarker associated with ecosystem collapse during the lower Triassic, and its ratio relative to the C34 n-alkane was elevated in facies that contain abundant microbialites. Mercury (Hg) to total reduced inorganic sulfur (TRIS) and Hg to total organic carbon (TOC) ratios are positively correlated, supporting the development of euxinia as sulfide sequesters Hg. The high Hg/TRIS values in microbialite facies support mat development with high Hg concentrations. The values of δ13COM and δ34S were isotopically lighter in microbialite facies when compared with mudstones formed under PZE, although samples deposited under oxic conditions showed the isotopically lightest δ13COM and isotopically heaviest δ34S. The variation in δ13COM probably reflects the different carbon fixation pathway of various sulfur bacteria, while it appears that the difference of δ34S values between PZE and microbialites is a result of differences in the microbial community structure and the higher relative abundance of purple sulfur bacteria. In addition, fluctuations between PZE and oxic conditions were identified throughout the sampled intervals attributed to fluctuations in the depth of chemocline. Under the shallower chemocline, PZE developed widely in the basin, even in shallower waters. Under the deeper chemocline PZE was absent or limited to deeper water, and oxic conditions developed in shallower water. The fluctuations of PZE and oxic conditions in the northern Perth Basin suggest the development of multiple episodes of harsh environmental conditions after the end-Permian mass extinction, similar to those identified in other regions (e.g., Meishan in China and Peace River in Canada).